Spatial Variability of Tidal Characteristics in Bintan Coastal Waters: A Case Study of Moco Port, Bakau Bay, and Tanjung Uban Port - M. Hasbi Sidqi Alajuri; Muhammad Zainuddin Lubis (Politeknik Negeri Batam, 2025)
Tidal dynamics play a crucial role in coastal processes, port operations, and coastal management, particularly in regions characterized by complex oceanographic interactions such as Bintan Island, Riau Islands Province, Indonesia. This study analyzes the spatial variability of tidal characteristics in the coastal waters of Bintan Island at three observation sites, namely Bakau Bay, Tanjung Uban Port, and Moco Port, using global tidal prediction data generated by MIKE Powered by DHI and harmonic analysis based on the Admiralty method. Eight principal tidal constituents (M₂, S₂, K₁, O₁, N₂, P₁, K₂, and Q₁) were examined, and tidal types were classified using the Formzahl number. The results reveal clear spatial variability in tidal harmonic characteristics despite the close geographic proximity of the sites, with the M₂ constituent dominating tidal behavior at all locations, indicating strong lunar control. Significant contributions from diurnal constituents (K₁ and O₁) result in mixed tidal regimes, with Formzahl values of 1.10 at Bakau Bay, 0.66 at Tanjung Uban, and 1.29 at Moco, classifying all sites as mixed tides with a predominance of semidiurnal components. Variations in tidal amplitudes are closely related to local coastal morphology and exposure to open waters, with Tanjung Uban exhibiting the strongest tidal influence. This multi-location analysis provides a comprehensive understanding of spatial tidal variability in Bintan coastal waters and supports coastal planning, port management, and hydrodynamic modeling in the region.